Use of the Patient-Reported Outcomes Measurement Information System (PROMIS) for Operative Shoulder Outcomes. Issue 6 (16th June 2020) - Schwarz, Ilona; Smith, John-Rudolph H.; Houck, Darby A.; Frank, Rachel M.; Bravman, Jonathan T.; McCarty, Eric C.
Background: Few studies have investigated the relationship between the Patient-Reported Outcomes Measurement Information System (PROMIS) and legacy patient-reported outcome (PRO) measurements. Purpose: To compare patient-reported outcomes from the PROMIS physical function (PF) and upper extremity (UE) platforms against one another and against legacy PRO measurements to assess the potential strengths and weaknesses of the National Institutes of Health PROMIS initiative and expand on the use of PRO measurements in clinical orthopaedic practice. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic search of the PubMed, Embase, and Cochrane Library databases was conducted following PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) guidelines. All English-language studies published between 2017 and 2019 using PROMIS to evaluate patients for shoulder surgery were analyzed. PROs were compared based on survey administered and the shoulder condition being investigated. Study quality was evaluated using the Modified Coleman Methodology Score and the Methodological Index for Non-Randomized Studies score. Results: We included 9 studies (5 studies were level 2; 3 studies were level 3; 1 study was level 4) encompassing a total of 1130 patients (60.2% male; mean age, 52.6 ± 16.5 years; mean BMI, 29.8 ± 2.8 kg/m 2 ). Of these, 6 studies administered the PROMIS PF, and 6 studies administered the PROMIS UE. The strongest correlation was between PROMIS PF computer adaptive test and the 36-Item Short Form Health Survey Global Health (SF-36 GH) ( r = 0.75). The highest overall correlation with the PROMIS UE was found with the American Shoulder and Elbow Surgeons (ASES) Shoulder Score ( r = 0.70). The lowest correlations were found between PROMIS PF and the Marx Shoulder Activity Scale ( r = 0.08) and the PROMIS UE and the Marx Shoulder Activity Scale ( r = 0.18). Conclusion: From available data, the PROMIS PF and PROMIS UE were most closely correlated with outcomes measured by the SF-36 GH. The PROMIS UE alone was most correlated with ASES Shoulder Score. Thus, either PROMIS PF or UE may provide a possible alternative to legacy PRO measurements but with a lower overall number of questions and higher generalizability. Future research should compare the time and question burden of the various PROMIS platforms with a more consistent evaluation of standard PRO measurements.